SIMULASI SISTEM PEMANTAUAN AIR SUNGAI BERBASIS INTERNET OF THINGS DAN KONTROL LOGIKA FUZZY - Hendrawan, Satya Arisena; Harun, Rofiq; Amirah, Amirah (STMIK BINA PATRIA, 2025)
This study aims to develop a river water hazard monitoring system based on the Internet of Things (IoT) and fuzzy logic. This system is designed to help the community in identifying the level of danger of river flows. By using ultrasonic sensors and Arduino Uno microcontrollers, Cisco Packet Tracer simulation, Fuzzy logic, and visualization using Proteus software. This system is capable of monitoring water levels in real-time, providing early warning notifications with a Fuzzy Logic approach to improve accuracy and response to critical conditions. The study uses the ADDIE development model, problem analysis using SWOT (Strength, Weakness, Opportunity and Threat), Feasibility Analysis using TELOS Analysis which analyzes five main aspects, namely Technical, Economic, Legal, Operational, and Schedule. The results of the Black Box test show that each function in the system works according to user needs. Based on the results of the UAT test, the average overall score is 4.51 (Very Good category). This means that the water level monitoring system developed with fuzzy logic received positive feedback from respondents. This system is considered accurate in detecting water levels, easy to use, and reliable in various environmental conditions.Keywords: Internet of Things, fuzzy logic, ultrasonic, Arduino, SWOT, TELOS